The Role of Artificial Intelligence (Chat GPT) in the Development of Technology and Communication - Rohmah, Salwa Nur; Haqqu, Rizca (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research investigates the role of ChatGPT in human-machine communication, focusing on interaction attributes and user perceptions. The study employs qualitative methods, including interviews with ChatGPT users, word cloud analysis using NVivo 12 Pro, and observation of interactions. Results highlight five frequently occurring codes: